Maintenance of dynamic single-legged stability with delayed peroneal reaction time in collegiate footballers during a prolonged football simulation - Huang, S. Z. Y.; Shan, W.; Fong, D. T. P. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to examine the change of peroneal reaction time and dynamic single-legged stability during a prolonged football match simulation. 12 collegiate footballers participated a Loughborough intermittent shuttle run protocol, within which peroneal reaction time and dynamic single-legged stability were measured to record the change. Results showed that during a prolonged fatiguing protocol, the peroneal reaction time increased significantly, whereas two indicators of the dynamic single-legged stability, root mean square of the mediolateral ground reaction force in 0.4 second of landing and late dynamic mediolateral ground reaction force, remained unchanged. The outcome indicated that the body might adopt different mechanism to maintain sensorimotor control in fatigue state.